A numerical study on methanol steam reforming reactor utilizing engine exhaust heat for hydrogen generation. (3rd November 2021) - Srivastava, Alankrit; Kumar, Parmod; Dhar, Atul
Abstract: Internal combustion engines are used in most vehicles around the world to power the transport sector. Efficiency improvement, emission reduction, and utilization of alternative fuels are the main aspects of current IC engine research. Hydrogen-enhanced combustion proved to be one of the efficient ways to achieve such goals. But the problem lies in the storage of hydrogen for the transportation sector, and on-board fuel reforming is a promising option for solving this issue. It deals with transforming a suitable liquid fuel (methanol) into an H2 -rich gas using a catalytic conversion process. For sustaining the reforming reaction, the required heat energy is taken from engine exhaust waste heat, this process is known as thermochemical recuperation. Number of studies on the reformers utilized for on-board hydrogen generation using engine exhaust heat are limited in the literature. The present study investigates the performance of a reactor that uses the exhaust gas heat energy for sustaining the reforming reaction. A numerical analysis was performed over a selected reactor where exhaust gases were flowing at one side, while on the other, the reforming reaction was taking place with the help of heat provided by high-temperature exhaust gases. A packed bed-type reactor was chosen for the current study and a parametric study was conducted where the effects of various operating parameters on both reacting and heating sides on the reactor's performance were investigated. It was found that temperature was the most influential inlet parameter among others. Steam/Carbon ratio and flow configuration had a negligible effect on the hydrogen yield as well as methanol conversion. Reactant inlet velocity increment revealed a significant drop in methanol conversion as it reduces the residence time for reforming reaction in the catalyst zone. Highlights: Hydrogen-enhanced combustion for improving engine performance and emission reduction. Solving problem of hydrogen storage through on-board generation using methanol reforming. Utilizing engine exhaust heat for driving reforming reaction: Thermochemical recuperation. Reformer design and conducting numerical study. Focusing on methanol conversion and H2 - yield dependency by carrying parametric study.